A new species of the genus Eurycotis Stål (Blattodea, Blattidae) from the eastern region of Cuba - Gutiérrez, Esteban (Zootaxa, 2025)
A new species, Eurycotis armasi sp. nov. from the eastern region of Cuba (West Indies) is described. A taxonomic diagnosis is provided to distinguish the new taxon from the closest previously known species of the genus, E. galeoides Rehn & Hebard, 1927, and E. ferrumequinum Rehn & Hebard, 1927. The 19 Cuban species of the genus are summarised in a table with the respective authors, the years of publication and the type localities. Knowledge about the diversity of Eurycotis in the Cuban Archipelago increases to 20 species. The distribution of species and the future increase in diversity of the genus on the island are discussed.